Personal resilience factors protect against distressing auditory hallucinations: A study comparing psychotic patients with auditory hallucinations, non-patients with auditory hallucinations, and healthy controls. (August 2020) - Laloyaux, Julien; Collazzoni, Alberto; Hirnstein, Marco; Kusztrits, Isabella; Larøi, Frank
Highlights: We examined the role of resilience in auditory hallucinations. We explored whether resilience is related to the beliefs about hallucinations. Personal resilience factors protect against distressing auditory hallucinations. Interpersonal factors do not seem to have an impact. Personal resilience factors represent a new treatment target. Abstract: Although studies have identified several risk factors for the development of psychotic disorders, potential protective factors – such as resilience – have rarely been examined. Studies suggest that the negative beliefs people hold about their Auditory Hallucinations (AH) may be an indicator of a need for care. However, the reason why certain people do not develop negative beliefs is unclear but may be related to resilience. The present study aimed to examine the role of resilience in AH by comparing psychotic patients with AH, non-patients with AH, and healthy controls without AH. Another aim was to explore whether resilience is related to the beliefs people hold about their AH. Results revealed that patients with AH and non-patients with AH had similarly weak interpersonal resilience factors compared to healthy controls without AH. In contrast, patients with AH showed weak personal factors of resilience compared to both non-patients with AH and healthy controls without AH. Patients with AH had more negative and fewer positive beliefs about their AH than non-patients with AH. Finally, the personal factors of resilience were related to the beliefs about AH. These results showed that personal factors of resilience are decisive variables influencing the need for care in people experiencing AH and thus represent an important treatment target.